Effect of Low Temperature RF Plasma Treatment on Electrical Properties of Junctionless InGaAs MOSFETs. (1st January 2019) - Gomeniuk, Y. V.; Gomeniuk, Y. Y.; Rudenko, T. E.; Okholin, P. N.; Glotov, V. I.; Nazarova, T. M.; Djara, V.; Cherkaoui, K.; Hurley, P. K.; Nazarov, A. N.
Abstract : In this paper, we study the effect of low-temperature RF plasma treatment in forming gas (10%H2 +90%N2 ) on the electrical characteristics of junctionless MOSFETs with n- In0.53 Ga0.47 As channel and an Al2 O3 gate dielectric. The impact of plasma power density on the device parameters is investigated. It is found that RF plasma annealing with a low power density (0.5 W/cm 2 ) at 150°C for 10 min provides substantial improvement of source/drain contacts resistance and the carrier mobility resulting in a considerable increase of the on-state current and transconductance. It also improves the subthreshold slope and reduces the fixed positive charge in Al2 O3 under the gate, shifting the threshold voltage toward positive values. It is demonstrated that non-thermal factors play a principle role in modification of electrical properties of the JL MOSFETs under RF plasma treatment. Such treatment may be an efficient tool for the improvement of the performance of the advanced MOSFETs with III-V channel materials.